Diagnostic and therapeutic pathway for pain in a Continuing Care setting: a survey at an Italian Continuing Care Service - Piroli, A.; Leuter, C.; Fusco, L.; Biccirè, D.; Paladini, A.; Testa, R.; Marinangeli, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Law no. 38 of 15 March 2010 ensures and governs the access to the palliative care and pain management network for patients who require it. The professional roles involved in the project have been identified by the law, with the specific experience and expertise in the field of palliative care and pain management, by allocating a meaningful role to general practitioners (GPs). For this reason, an important direct training plan has been drawn up that GPs can count on for dedicated refresher courses to increase and deepen their knowledge in this specific clinical field. If the role of the GPs in the pain management and palliative care network was well-defined by the law, we cannot say the same for the Continuing Care Physician (CCP), a role that only partially overlaps that of the GP. The study observed the response of a Continuing Care Service (CCS) to the demand for services from patients with pain-related problems. The role of the CCP is, therefore, outlined in the pain therapy care network by observing the services provided to patients experiencing pain that is understood as being a non-deferrable problem. Methods. A survey was conducted at the CCSs site in Aquila, AS-01 Abruzzo. For this reason, the attending physician records the data of patients who consult the CCSs for pain-related problems on an appropriate questionnaire. The survey period covered a total of 68 days (1 January - 8 March 2020). Results. One hundred sixty five sheets were completed; females were more represented than males (57.6% v 42.4%) and the 36-65 age group appears most greatly represented (47.9%). One of the most frequent reasons for consulting the service is “musculoskeletal pain” (58.2%), followed by abdominal pain (15.8%). In the majority of patients, pain lasted from days (53.9%), with an average of approximately 3 days (3.1± 2.9), or hours in 40% of cases, with an average of over 6 hours (6.54±3.1). 88.5% of patients defined the level of pain experienced as “severe” (NRS=7-10), and the intensity of the pain associated with its repetitiveness (80.3% vs 92.6%) as “severe”, with a statistically significant difference in relation to nonrepetitiveness cases (p=0.02). 66.1% of patients said that they had taken analgesics independently, with nonsteroidal anti-inflammatory drugs (NSAIDs) the most frequently taken (53.5%). Patients who turned to the CCS received a pharmacological prescription in almost all cases. NSAIDs, specifically, were the most prescribed medicines (64.8%), followed by muscle relaxants (29.7%). Tramadol was the most represented among opioids, which was prescribed in 7.9% of cases. Just 6.1% of patients were entered into the regional pain management network. Conclusions. The results of the survey show that a large number of patients turn to the CCS to resolve painful symptoms of various natures. The study offers some food for thought concerning the role of CCPs and the importance of providing for their inclusion in the pain therapy clinical and training pathways provided for by Law 38/2010. This would ensure its more effective implementation and, therefore, better care for patients experiencing painful pathologies.